Learning Management of Religious Moderation in the Digital Era: A Case Study at the University - Agung Ilham Prastowo; Zaki Afifi; Muh. Kholid Ramadhanzi; Alfi Lubbi Zodan (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
In the digital era, university students are increasingly exposed to radicalism and extremism through social media platforms, posing a significant challenge to national and global efforts to promote moderate religious values.This research aims to reveal the paradigm and the implementation of learning management for religious moderation at Muhammadiyah University of Surakarta (UMS)  in the digital era. The method used in this research is qualitative with a case study approach. Data sources were obtained from interviews, observations, and documentation, while data analysis techniques include data condensation, data presentation, and conclusion drawing/verification. The results of this study indicate that the learning management of religious moderation at Muhammadiyah University of Surakarta is built on the paradigms of inclusiveness, progressiveness, and tolerance. These concepts are implemented through the management curriculum and the strategy of teaching. The study contributes to theoretical and practical discussions on managing religious education in universities, emphasizing the importance of adapting to digital transformations while promoting moderate religious values.